Poe and the visual arts - Cantalupo, Barbara (The Pennsylvania State University Press, 2014)
"Explores visual allusions in the writings of Edgar Allan Poe to paintings and sculptures he saw in Philadelphia and Manhattan. Examines how his writings relate to the visual culture of his time"--Provided by publisher
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Technique.; Poe, Edgar Allan, -- 1809-1849 -- Aesthetics.; Poe, Edgar Allan, -- 1809-1849 -- Criticism and interpretation.; Poe, Edgar Allan, -- 1809-1849 -- Knowledge -- Art.; Poe, Edgar Allan, -- 1809-1849; Art in literature.; Art and literature -- United States -- History -- 19th century.; Art dans la littérature.; Art et littérature -- États-Unis -- Histoire -- 19e siècle.; LITERARY CRITICISM -- American -- General.; Aesthetics; Art; Art and literature; Art in literature; Technique; United States; 1800-1899; Criticism, interpretation, etc.; History